2022
DOI: 10.1371/journal.pone.0272080
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of PD-L1 expression in patients with salivary gland carcinoma: A systematic review and meta-analysis

Abstract: Background Although programmed cell death-ligand 1 (PD-L1) has been recognized as a potential marker in several cancers, the relationship between PD-L1 expression and survival in patients with salivary gland carcinoma (SGC) has remained unclear. We aimed to evaluate the association of PD-L1 expression with clinicopathological features and prognosis in SGC patients. Methods The databases Ovid Medline, PubMed, Scopus, and EMBASE were searched for relevant studies that detected PD-L1 expression in SGC. The meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 75 publications
(150 reference statements)
0
2
0
Order By: Relevance
“…In OSCC, Levounel et al [27] found that overexpression of PD-L1 had a worse survival measured as DSS and DFS. The other meta-analysis, done by Wu L et al [32], suggest that PD-L1 may play an important role as an effective marker of poor prognosis in salivary gland carcinomas. On the contrary, X.…”
Section: Discussionmentioning
confidence: 99%
“…In OSCC, Levounel et al [27] found that overexpression of PD-L1 had a worse survival measured as DSS and DFS. The other meta-analysis, done by Wu L et al [32], suggest that PD-L1 may play an important role as an effective marker of poor prognosis in salivary gland carcinomas. On the contrary, X.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to standardize the method to detect PD-L1 expression and to apply PD-L1 as an accurate prognostic marker in SGCs. Wu et al conducted a meta-analysis regarding the association between PD-L1 positivity and prognosis in SGCs [ 74 ]. This study revealed that high PD-L1 expression is associated with poor OS and DFS, indicating the importance of PD-L1 in SGC progression.…”
Section: The Expression Rates and Prognostic Ability Of Immune Checkp...mentioning
confidence: 99%
“…1,10,11,[20][21][22] Although multiple reviews have been published on salivary gland tumours, 7,10,13,18,23 including CXPA, 10,13,23,24 it has been a decade since the last dedicated systematic review pertaining to molecular genetics in CXPA was published. 1 Existing reviews on important biomarkers, such as PD-L1, 25 PLAG1, 12 and other targeted therapies, 18,19 do not address CXPA as a distinct entity. Aside from HER2, 22 the exact role of molecular markers in the diagnosis and treatment of CXPA is yet to be precisely defined.…”
Section: Introductionmentioning
confidence: 99%